Tetramethylpyrazine Preserves the Integrity of Blood-Brain Barrier Associated With Upregulation of MCPIP1 in a Murine Model of Focal Ischemic Stroke - Jin, Zhuqing; Liang, Jian; Kolattukudy, Pappachan E. (Frontiers in Pharmacology, 2021)
Tetramethylpyrazine (TMP), a prominent ingredient of Chinese herb Ligusticum chuanxiong Hort, is known to suppress neuroinflammation and protect blood-brain barrier (BBB) integrity. We investigated whether monocyte chemotactic protein-induced protein 1(MCPIP1), a newly identified zinc-finger protein, plays a role in TMP-mediated anti-inflammation and neuroprotection. Male C57BL/6 mice were subjected to focal cerebral ischemia induced by middle cerebral artery occlusion (MCAO) for 2 hours, followed by reperfusion for 24 hours. TMP (25 mg/kg or 50mg/kg) or vehicle was administered intraperitoneally 12 hours before and post MCAO. The TMP significantly upregulated MCPIP1 in the ischemic brain tissues and effectively inhibited extravasation of fluorescein isothiocyanate (FITC)-dextran, resulting in attenuation of brain edema. These effects were associated with a significant reduction in levels of inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and MMP-9 in the ischemic brain tissues. The TMP upregulated the expression of MCPIP1 in primary cultures of neurons and protected against oxygen–glucose deprivation-induced neuron death, while this neuroprotective effect of TMP was abolished by knockdown of MCPIP1 using MCPIP1-specific siRNA. These results demonstrate that TMP preservation of BBB integrity is associated with its anti-inflammatory activity. The effect of TMP is mediated, at least in part, via upregulation of MCPIP1 in the ischemic brain.